Preparation and characterization of bioinert amphiphilic P(VDF-co-CTFE)-g-POEM graft copolymer. Issue 10 (2nd July 2020) - Patel, Rajkumar; Patel, Madhumita; Sung, Jung-Suk; Kim, Jong Hak
ABSTRACT: Hydrophobic poly (vinylidene fluoride-co-chlorotrifluoroethylene) P(VDF-co-CTFE) was used as the polymer backbone to graft poly (oxyethylene methacrylate) (POEM) by atom transfer radical polymerization. Synthesis of graft P(VDF-co-CTFE)-g-POEM copolymer was confirmed by fourier transfer infrared spectroscopy (FTIR) and proton nuclear magnetic resonance ( 1 H-NMR). The hydrophilicty of grafted membrane increased with increasing ingrafting of POEM as characterized by contact angle measurement. Transmission electronmicroscopy (TEM) study reveals the microphase separated morphology of P(VDF-co-CTFE)-g-POEM copolymer. Adhesion of gram-positive and negative bacteria and mouse embryonic fibroblast (MEF) cell on the membrane surface were observed by SEM that showed the enhancement of bioinert properties with the increase in the POEM grafting. Bioinert properties were further confirmed by protein adsorption behavior. Graphical abstract: